Analysis of the relationship of household waste to Cikapundung river water pollution around Wastukencana street - Tamba, Rhodentia; Surtikanti, Hertien Koosbandiah (Asian Journal of Toxicology, Environmental, and Occupational Health, 2024)
Cikapundung river, a tributary of the heavily polluted Citarum River, faces significant contamination due to human activities, particularly those near its vicinity. Without community awareness to preserve the river's ecosystem, its water quality deteriorates. This study aims to analyze the correlation between household waste generated by nearby residents and the pollution of Cikapundung river near Wastukencana Street. Employing a descriptive-qualitative method, the research involved observation, surveys, and direct interviews with local residents. Samples were selected using purposive sampling based on specific considerations related to the research objectives. Observations revealed both organic and inorganic waste in the river, leading to sedimentation. Additionally, numerous riverside structures were found filled with garbage, indicating a high density of construction. Interviews highlighted that residents refrain from using the river water for daily activities due to its poor quality, colored and contaminated with chemicals and waste. The majority rely on piped water from the water utility (PDAM), with many lacking septic tanks, leading household wastewater to directly flow into Cikapundung river. Consequently, household waste significantly contributes to the river's pollution, exacerbated by a lack of public awareness, knowledge about waste management, and governmental attention to environmental preservation.